Dental Erosion from an Excess of Vitamin C - Priya Bahal; Serpil Djemal (Case Reports in Dentistry)
Acid erosion of enamel is the chemical dissolution of the superficial layers of teeth without the presence of bacteria. If the presence and exposure of a demineralising agent such as vitamin C is frequent and prolonged, it can lead to significant tooth wear. This case report discusses one such presentation and as a result of the occlusal relationship, this serves to effectively demonstrate the localised effects of vitamin C-induced acid erosion. The management of localised tooth wear with composite restorations utilising the Dahl principle to replace lost tooth tissue is also reported. Clinical Relevance. Patients should be made aware of the erosive nature of chewable vitamin C tablets and their potentially harmful effects on the dentition if consumed in excess. Objective Statement. The reader should understand the clinical implications of an excessive intake of vitamin C. This demonstrates the importance of the manufacturer’s instructions and the clinician’s role in advising patients with regard to the correct therapeutic doses.